Effects of menstrual cycle on hemodynamic and autonomic responses to central hypovolemia - Shankhwar, Vishwajeet; Urvec, Janez; Steuber, Bianca; Schmid Zalaudek, Karin; Saloň, Adam; Hawliczek, Anna; Bergauer, Andrej; Aljasmi, Khawla; Abdi, Asrar; Naser, Asmaa; Himeidi, Maya; Alsuwaidi, Hanan; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Estrogen and progesterone levels undergo changes throughout the menstrual cycle.Existing literature regarding the effect of menstrual phases on cardiovascular and autonomic regulation during central hypolemia is contradictory.This study aims to explore the influence of menstrual phases on cardiovascular and autonomic responses in both resting and during the central hypovolemia induced by lower body negative pressure (LBNP). This is a companion paper, in which data across the menstrual phases from healthy young females, whose results are reported in Shankwar et al ( 2023), were further analysed.The study protocol consisted of three phases: 1) 30 minutes of supine rest; 2) 16 minutes of four LBNP levels; and 3) 5 minutes of supine recovery. Hemodynamic and autonomic responses (assessed via heart rate variability, HRV) were measured before-, during-, and after-LBNP application using Task Force Monitor® (CNSystems, Graz, Austria). Blood was also collected to measure estrogen and progesterone levels.In this companion paper, we have exclusively assessed 14 females from the previous study